Satiety responsiveness but not food reward is modified in response to an acute bout of low versus high intensity exercise in healthy adults. (1st February 2020) - Thivel, D.; Fillon, A.; Genin, P.M.; Miguet, M.; Khammassi, M.; Pereira, B.; Boirie, Y.; Duclos, M.; Drapeau, V.; Blundell, J.E.; Tremblay, A.; Finlayson, G.; et al.
Abstract: To compare the effect of iso-caloric low and high intensity exercises on Satiety Quotient and Food Reward in response to a fixed meal in healthy young adults. Anthropometric measurements, body composition (BIA), aerobic capacity (VO2 max) and food preferences were assessed in 19 healthy normal-weight young adults (21 ± 0.5 years old, 10 men). They randomly completed 3 experimental sessions: i) control session without exercise (CON); ii) High Intensity exercise session (HIE); iii) Low intensity exercise session (LIE). Thirty minutes after exercise or rest, then received a fixed lunch. Food reward (Leeds Food Preference Questionnaire) was assessed before and after the meal. Appetite sensations were assessed at regular intervals, SQ was calculated from the lunch meal and self-reported food intake was collected for the rest of the day. Mean body weight was 66.7 ± 9.2 kg, body mass index was 22.3 ± 2.9 kg/m 2 and FM% was 18.7 ± 6.8%. Appetite feelings did not differ between conditions and were not affected by exercise. SQ for satiety was not different between conditions. SQ hunger on CON was significantly higher than on LIE and HIE (p ≤ 0.05) with no difference between exercise conditions. SQ for desire to eat was significantly higher on CON versus HIE (p ≤ 0.01) with no differences between CON and LIE and between exercise sessions. SQ PFC was significantly lower on HIE compared with CON (p = 0.02) with no differences between LIE and CON and between LIE and HIE. Food reward was not significantly different between the three condition as well as self-reported total food and macronutrient intake for the rest of the days. Acute exercise, depending on its intensity, might affect the satiating response to food intake in healthy adults, without altering food reward.